Diseminasi Inovasi BoosterUmpan Beku dan Teknologi Perangkap Krendet Bertingkatuntuk Pemanfaatan Sumber Daya Krustaseadi Desa Loji, Sukabumi - Zulkarnain, Zulkarnain; Wahju, Ronny Irawan; Purwangka, Fis; Mawardi, Wazir; Budiman, Muhamad Syarif; Kasma, Ende; Permana, Arik; Ramadhan, Muhammad Haykal; Aldanita, Ega (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2025)
The community empowerment program for the fishermen who are members of KUB Berkah Sagara aims to disseminate the innovation of frozen bait booster and 2-deck krendet trap technology as additional fishing gear in their fishing operations. The activities were carried out at Loji Village and the IPB Palabuhanratu Marine Field Station. Activities were carried out using FGD methods, interviews, technical training and trials of catching crustaceans. The KUB Berkah Sagara Partner Fishermen are between 30 and 59 years of age and have with a formal education level between elementary and vocational/high school. Skills fishing have been passed down from generation to generation and they are not yet aware of the innovation of the 2-deck krendet trap and the frozen bait booster innovation. After the training activities, the fishermen finally understood the 2-deck krendet trap and frozen bait booster innovation. Fishermen carry out trial activities to catch crustaceans alternately on each trip. The 2-door 2-deck krendet trap provides a higher catch of crustaceans in term of the number of tails and weight compared to traditional, 1-door and 3-door of 2-deck krendet trap. The average distribution of crustaceans caught in 2-deck krendet trap was more than 70% in the bottom trap and <30% in the upper trap. The use of a 2-door of 2-deck krendet trap should be operated with a single buoy colony system with a ratio between the number of 2-deck krendet traps and the number of frozen bait boosters of 5:1, where the frozen bait booster is placed in a collapsible trap and the 2-deck krendet trap uses trash fish bait, such as sardine or pony fish.